Interactional practices in person‐centred care: Conversation analysis of nurse‐patient disagreement during self‐management support. (28th March 2021) - Forsgren, Emma; Björkman, Ida
Abstract: Background: Person‐centred care implies a change in interaction between care professionals and patients where patients are not passive recipients but co‐producers of care. The interactional practices of person‐centred care remain largely unexplored. Objective: This study focuses on the analysis of disagreements, which are described as an important part in the co‐production of knowledge in interaction. Design: A qualitative exploratory study using conversation analysis. Setting and participants: Data were collected from a nurse‐led person‐centred intervention in a hospital outpatient setting. Interactions between adult patients with irritable bowel syndrome (n = 17) and a registered nurse were audio‐recorded. COREQ guidelines were applied. Results: Disagreements were found after demonstration of the nurse's or patients' respective professional or personal knowledge. Disagreements were also evident when deciding on strategies for self‐management. Although negotiations between opposing views of the nurse and patient were seen as important, the patient generally claimed final authority both in knowing how IBS is perceived and in the right to choose self‐management strategies. The nurse generally oriented towards patient authority, but instances of demonstration of nurse authority despite patient resistance were also found. Discussion and conclusions: This study provides information on how co‐production of knowledge and decisions occur in the context of a person‐centred care intervention. Negotiations between nurse and patient views require a flexible approach to communication, adapting interaction to each context while bearing in mind the patients having the final authority. To facilitate co‐production, the patient's role and responsibilities in interaction should be explicitly stated.